Trends towards Internationalisation of Higher Education in Europe. - Tonenchuk, Tetiana; Osovska, Iryna (My University, 2023)
Today diversity, inclusiveness, equality and internationalisation in the higher education sector have become more significant than ever before. Institutions of higher education prepare themselves for the changes driven by the national, European and global context. Analyzing this transformation, we suggest an overview of the trends towards internationalisation of higher education in Europe. Three develop-ments taking place simultaneously can be clearly observed. Firstly, European higher education faces a more market-oriented approach to education andtraining. Secondly, the internationalisation of higher education has been boosted by a series of agreements made at the level of the European Commission. Lastly, the quality assessment is slowly being transformed from an institution-centered national process to international accreditation.
Keywords: higher education; alliance; European education